Crowd dynamics, policing and hooliganism at Euro 2004 - Stott, Clifford John T. (UK Data Service, 2019)
This research project analysed the impact of public order policing strategies upon levels of 'hooliganism' at the Union of European Football Associations (UEFA) European Championships in Portugal in June and July 2004 (Euro 2004). The project combined two methodological approaches, structured observation and ethnography, to collect data on police and fans during the event. The research was used to address three specific issues. Firstly, it aimed to understand the psychological processes and intergroup dynamics underlying both the presence and absence of 'disorder' in the context of international football. Secondly, it was used to evaluate the effectiveness of police strategies and tactics used to prevent crowd disorder, and finally, it attempted to develop the relationship between science and practice in the realm of public order by providing an empirically-based approach to the safety and security planning of future international football tournaments.